The Spellman files [large type] - Lutz, Lisa (Lutz, Lisa. Spellman novel., 2007)
Meet Isabel "Izzy" Spellman, private investigator. This twenty-eight-year-old may have a checkered past littered with romantic mistakes, excessive drinking, and creative vandalism; she may be addicted to Get Smart reruns and prefer entering homes through windows rather than doors -- but the ups hot is she's good at her job as a licensed private investigator with her family's firm, Spellman Investigations. Invading people's privacy comes naturally to Izzy. In fact, it comes naturally to all the Spellmans. If only they could leave their work at the office. To be a Spellman is to snoop on a Spellman; tail a Spellman; dig up dirt on, blackmail, and wiretap a Spellman. Part Nancy Drew, part Dirty Harry, Izzy walks an indistinguishable line between Spellman family member and Spellman employee. Duties include: completing assignments from the bosses, aka Mom and Dad (preferably without scrutiny); appeasing her chronically perfect lawyer brother (often under duress); setting an example for her fourteen-year-old sister, Rae (who's become addicted to "recreational surveillance"); and tracking down her uncle (who randomly disappears on benders dubbed "Lost Weekends"). But when Izzy's parents hire Rae to follow her (for the purpose of ascertaining the identity of Izzy's new boyfriend), Izzy snaps and decides that the only way she will ever be normal is if she gets out of the family business. But there's a hitch: she must take one last job before they'll let her go -- a fifteen-year-old, ice-cold missing person case. She accepts, only to experience a disappearance far closer to home, which becomes the most important case of her life.